A preliminary investigation of Nigerian Gmelina arborea and Bambusa vulgaris for pulp and paper production - Akeem Azeez, Mayowa; Andrew, Jerome E.; Bruce Sithole, B. (Maderas. Ciencia y Tecnología, 2016)
Two common Nigerian-grown biomasses, gmelina (Gmelina arborea) and bamboo (Bambusaa vulgaris) have been pulped and their fibre characteristics and paper properties examined. The results of their chemical compositions showed some fair similarities. The amount of glucose in the pulps of both biomasses indicated their suitability as lignocellulosic materials for pulping. Their pulp yield ranged between 48,0-54,1%, which fell within the acceptable range for good pulpwoods. The analysis of their fibre dimensions revealed that bamboo fibre has a wider fibre length distribution and higher fine length content. Gmelina and bamboo had weighted mean fibre lengths of 0,93 and 2,07 mm and mean fibre widths of 24,1 and 16,9 μm, respectively. The Runkel ratios of the samples were 0,4 (gmelina) and 0,9 (bamboo): this is indicative of their suitability for paper making. Mechanical properties of handsheets obtained from gmelina compared fairly well with South African pulpwoods (Eucalyptus grandis and Pinus paluta). Bamboo exhibited better tear index values than these woods but with lower sheet density and tensile index. These properties were significantly improved in handsheets obtained from blends of gmelina and bamboo, raising the prospect of producing paper from blends of both raw materials in Nigeria.